IL-6, TNF-α and IL-12p70 levels in patients with colorectal cancer and their predictive value in anti-vascular therapy - Zheng, Jingxian; Wang, Xiaojie; Yu, Jiami; Zhan, Zhouwei; Guo, Zengqing (Frontiers in Oncology, 2022)
We aimed to analyze the levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and interleukin-12 (IL-12p70) in colorectal cancer and evaluate the predictive significance of clinical efficacy of patients with colorectal cancer treated with anti-vascular therapy combined with chemotherapy. A retrospective study of 162 patients with colorectal cancer in Fujian Medical University Hospital was conducted from January 2019 to December 2020. A comparative analysis of the levels of IL-6, TNF-α and IL-12p70 between the two groups were studied. The relationship between the levels and the clinical characteristics of patients was observed; the factors affecting the levels of IL-6, TNF-α, and IL-12p70 in colorectal cancer patients were analyzed, and the predictive validity of the efficacy of anti-vascular therapy was evaluated. We observed that the individual expression levels of IL-6, TNF-α and IL-12p70 in the patients with colorectal cancer are related to lymph node metastasis, TNM staging, and degree of differentiation (P﹤0.05); however, they are irrelevant to the age, sex, and tumor location of patients with colorectal cancer (P﹥0.05). The multiple stepwise regression analysis indicates that lymph node metastasis and TNM staging are independent risk factors that correlate with IL-6 and IL-12p70 levels in colorectal cancer patients (P﹤0.01). The degree of differentiation was found to be an independent risk factor connected to TNF- α levels of patients with colorectal cancer. The change of IL-12p70 level could predict the validity of anti-vascular treatment for advanced colorectal cancer. When evaluated for combined expression, IL-6 and IL-12p70 in patients with colorectal cancer closely related to lymph node metastasis and TNM staging. IL-12p70 can be used as a predictor of anti-vascular therapy with colorectal cancer.